Ten minutes continuous recording lightning using broadband VHF interferometer. Issue 10 (15th November 2015) - Samy, Lotfy; Nakamura, Yoshitaka; Allam, Ahmed; Ushio, Tomoo; Kawasaki, Zen
Abstract A continuous recording system for digital signals associated with lightning discharge is designed to enhance lightning discharge processes understanding. The original VHF interferometer occasionally misses small amplitude impulses, and this disadvantage causes imperfect imaging of lightning progressions, especially positive breakdowns. To overcome this difficulty, the method of phase difference standard deviation of frequency components is applied. Numerical simulations and winter thunderstorm observations are presented to show and evaluate the capability of the new system.